Plant Regeneration Through Multiple Shoot Formation in Blackgram (Progressive Agriculture, 2013)
Blackgram (Vigna mungo L. Hepper, syn. Phaseolus mungo L.) is one of the four major pulse crops. So far, no reports of tissue culture studies aiming at genetic improvement of this crop are available in Bangladesh. The present study comprised of experiments for direct shoot regeneration and plantlet formation in blackgram. Shoot tip explants were cultured on different concentrations of BAP (1.0, 5.0 and 10.0 mg L-1) and Kinetin (1.0, 5.0 and 10.0 mg L-1). The highest percentage (85.00%) of multiple shoot initiation was observed in the MS medium supplemented with 5.0 mg L-1 kinetin. The regenerated shoots were transferred to rooting medium supplemented with different concentrations of NAA. A high frequency of 85% rooting was observed with 0.2 mg L-1 NAA. The rooted plants were transferred to pots for hardening.DOI: http://dx.doi.org/10.3329/pa.v18i2.17458 Progress. Agric. 18(2): 11 - 16, 2007